2017
DOI: 10.14417/ap.1156
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics: I don't like it! I like it! Very much, a little, not at all... Social support and emotions in students from 2nd and 3rd cycles of education

Abstract: This research analyses achievement emotions and their relationship to perceived classroom support (teacher and peers) as well as the effects of grade, achievement and gender on emotions in a specific subject domain: mathematics. The participants were 1.494 Portuguese students from the sixth and eighth grades who were asked about their perceptions of teacher and peer support and their achievement emotions towards mathematics (Boredom, Hopelessness, Anger, Anxiety, Enjoyment, Pride and Relief) in two different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…Furthermore, although our results are similar to those in past research among older students (Ahmed et al 2013;Mata et al 2017;Monteiro et al 2017), when comparing them with the results obtained by Vierhaus et al (2016) with German primary school students, some differences are found regarding enjoyment: the German research revealed high and stable levels of enjoyment from second to fifth grade. In our research, Portuguese students showed a decreasing pattern from third to fourth grade, similar to what was found for older students in diverse studies (Ahmed et al 2013;Mata et al 2017;Pinxten et al 2014).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, although our results are similar to those in past research among older students (Ahmed et al 2013;Mata et al 2017;Monteiro et al 2017), when comparing them with the results obtained by Vierhaus et al (2016) with German primary school students, some differences are found regarding enjoyment: the German research revealed high and stable levels of enjoyment from second to fifth grade. In our research, Portuguese students showed a decreasing pattern from third to fourth grade, similar to what was found for older students in diverse studies (Ahmed et al 2013;Mata et al 2017;Pinxten et al 2014).…”
Section: Discussionsupporting
confidence: 87%
“…However, enjoyment and boredom presented reversed emotional pathways: enjoyment decreased significantly and continuously, while boredom significantly increased. Overall, these results are similar to those identified in older students in both cross-sectional and longitudinal studies (Ahmed et al 2013;Mata et al 2017;Monteiro et al 2017;Vierhaus et al 2016), indicating that this pattern begins very early, even when students are at the beginning of their school process. Several reasons have been offered to explain these reverse patterns of positive and negative emotions throughout schooling, which are similar to the negative changes already identified in motivation research (Wigfield and Eccles 2000).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A few studies also examined gender differences regarding well-being at school, but the findings are not always consistent [15,23]. The literature on this issue is not conclusive: Coherently with results concerning the motivational domain, gender differences for wellbeing are usually different for different school domains and sometimes they concern only some components of school-related well-being [24][25][26].…”
Section: Well-being In the Transition From Primary School To Secondarmentioning
confidence: 99%